Pendidikan yang Membebaskan: Sebuah Reinterpretasi Filsafat Pendidikan Paulo Freire - Reni, Siti; Asbari, Masduki; Ramadhan, Mohamad Biazt (AGUSPATI RESEARCH INSTITUTA, 2024)
This article is a review which is a critical reading of a guidebook that inspires and provides motivation for readers entitled